2012
DOI: 10.1007/s10144-012-0358-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in population dynamics of the sand‐burrowing amphipodHaustorioides japonicus

Abstract: Densities of sandy beach organisms along coastlines often vary considerably even within small local scales. In order to understand the demographic basis of density variations in shore animals, we examined the population dynamics of the amphipod Haustorioides japonicus Kamihira, which is an ideal subject because it lacks a planktonic dispersal stage in its life history. Quantitative sampling at three adjacent sandy beaches along the Sea of Japan coast revealed that the spring density, i.e., the density of overw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Among them, two species, H. japonicus and H. munsterhjelmi, and four species, H. koreanus, H. latipalpus, H. indivisus, and H. nesogenes, are found in Japan and South Korea, respectively. Haustorioides japonicus occurs on the intertidal zones of sandy beaches on the coast of the Sea of Japan, Kyushu and Honshu; the coast of the Oshima Peninsula, Hokkaido; and the Pacific coast on the northeastern part of Honshu (Kamihira 2000, Kaneko & Omori 2003, Suzuki et al 2013, Takada et al 2016. Haustorioides munsterhjelmi is distributed only in the easternmost part of Hokkaido, and H. koreanus is most common on intertidal sandy beaches throughout the southern half of the Korean Peninsula, except for the east coast of South Korea (Jo 1988, Kamihira 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, two species, H. japonicus and H. munsterhjelmi, and four species, H. koreanus, H. latipalpus, H. indivisus, and H. nesogenes, are found in Japan and South Korea, respectively. Haustorioides japonicus occurs on the intertidal zones of sandy beaches on the coast of the Sea of Japan, Kyushu and Honshu; the coast of the Oshima Peninsula, Hokkaido; and the Pacific coast on the northeastern part of Honshu (Kamihira 2000, Kaneko & Omori 2003, Suzuki et al 2013, Takada et al 2016. Haustorioides munsterhjelmi is distributed only in the easternmost part of Hokkaido, and H. koreanus is most common on intertidal sandy beaches throughout the southern half of the Korean Peninsula, except for the east coast of South Korea (Jo 1988, Kamihira 2000.…”
Section: Introductionmentioning
confidence: 99%
“…A demographic study of H. japonicus in Niigata demonstrated that the populations increased from spring to summer as a result of multiple events of recruitment of juveniles; then, from fall to winter, recruitment did not occur and the populations decreased (Suzuki et al 2013). A similar seasonal life history was observed in E. chiltoni (Kaneko & Omori 2005): its recruitment occurred only in the warm season.…”
Section: Introductionmentioning
confidence: 79%
“…We investigated the zonation pattern in summer, but seasonal variations may be considerable (Brazeiro & Defeo 1996, Giménez & Yannicelli 1997. Because of the harsh wind-driven waves in winter (Naganuma 2000) and seasonal variations in abundance and vertical distribution of sandy beach macrofauna (e.g., A. kokuboi: Takahashi & Kawaguchi 1995, Donax semigranosus: Hasegawa & Yajima 2000, E. chiltoni: Kaneko & Omori 2005, H. japonicus: Kamihira 1992, Suzuki et al 2013, Tylos granuliferus: Kuramochi 2006, Talitridae: Tsubokura et al 1997, zonation patterns in winter may be different from the present results obtained in summer. Especially in winter, assemblage C2 may not be recognizable because of a decrease in the density of its indicator, H. japonicus (Suzuki et al 2013).…”
Section: Environmental Factors and Assemblagesmentioning
confidence: 99%